Effect of Training Method and Hemoglobin Level on Cardovascular Endurance of Siliwangi University Football Players - Ramdhan Nur Habibie; Sulaiman Sulaiman; Fajar Awang Irawan (JUARA : Jurnal Olahraga, 2023)
The purpose of this study was to analyze the influence of exercise methods, namely HIIT 10 minutes cardio workout and HIIT walk and run, on the cardiovascular endurance ability of football players, to analyze the effect of normal high and normal low haemoglobin levels on capacity cardiovascular endurance of football players, and to analyze the interaction of HIIT 10 minutes cardio workout and HIIT walk and run exercise methods and haemoglobin levels to cardiovascular endurance ability in unsil football players in 2022. This study used an experimental method with a 2x2 factorial design, a data analysis technique using Analysis Of Variance (ANOVA) at the signification level (α: 0.05). Results of this study: This is a HIIT 10 minutes cardio workout exercise method with an average VO2Max increase of 1.44, while the HIIT walk and run exercise method have an average of 1.35. Unsil United football SME players In 2022 who have high normal haemoglobin have an average increase in cardiovascular endurance ability greater than players who have low normal haemoglobin. Still, the results of cardiovascular endurance ability in unsil united football SMEs in 2022 showed no interaction because players with low haemoglobin levels get good VO2Max results. Of course, with high haemoglobin, there are also fewer VO2Max results because both methods of HIIT 10 minutes cardio workout and HIIT walk and run exercise with the same intensity and administration, so there is no interaction.